2022 32nd International Telecommunication Networks and Applications Conference (ITNAC) 2022
DOI: 10.1109/itnac55475.2022.9998374
|View full text |Cite
|
Sign up to set email alerts
|

Migration Strategy from C-Band Elastic Optical Network to C+L Multiband Optical Network

Abstract: Multi-band elastic optical network (MB-EON) is a promising technology to extend the bandwidth of the current elastic optical networks in the middle term. The migration from current networks to MB-EONs should be made carefully taking into account both the required cost and the bandwidth requirements. This paper focuses on the necessity of looking for a trade-off between the links to be upgraded during the migration from the standard C-band to the L-band and the acceptable level of capacity increase. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
1
11
0
2
Order By: Relevance
“…These last works, [30,31], assume an incremental traffic model, where new connections are established, but once established are never released. In [32], we proposed a heuristic algorithm for gradually upgrading the fibers of a network to support the C + L-bands. In contrast to [30,31], we assumed a dynamic traffic model, where connections are established but also released on user demand, and demonstrated that the supported traffic load can be significantly increased with a partial upgrade of the network links.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These last works, [30,31], assume an incremental traffic model, where new connections are established, but once established are never released. In [32], we proposed a heuristic algorithm for gradually upgrading the fibers of a network to support the C + L-bands. In contrast to [30,31], we assumed a dynamic traffic model, where connections are established but also released on user demand, and demonstrated that the supported traffic load can be significantly increased with a partial upgrade of the network links.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, we also proposed and compared two heuristics to solve the RBMLSA problem. Then, in [33], we introduced a novel integer linear programming (ILP) formulation to determine the set of fibers that should be upgraded to the C + L-bands (subject to a constraint on the maximum number of fibers that should be migrated), which generally outperforms the proposal in [32].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Na literatura, observam-se estratégias de alocação de banda em redes ópticas MB que utilizam atribuições fixas [2]- [4], [7]- [9], heurísticas [10]- [13] e técnicas de inteligência artificial [6], [14], [15]. Além disso, algumas consideram penalidades físicas por meio de modelagens analíticas [2]- [4], [9], [13] e outras por meio do alcance máximo [6], [7], [10], [11], [14], [15].…”
Section: Revisão Da Literaturaunclassified
“…Uzunidis et al [3] propuseram um algoritmo de roteamento, atribuição de modulação e espectro, estimando o impacto das penalidades físicas nas bandas de transmissão O, S, C e L. Para a etapa de alocação de banda, os autores seguiram a sequência: O → C → L → S. Hosseini et al [7] propuseram uma heurística para resolver o problema de roteamento, alocação de formato de modulação, banda e espectro (RMLBSA -Routing, Modulation Level, Band and Spectrum Assignment). Para isso, utilizaram o algoritmo que pré-selecionava k rotas para qualquer solicitação de chamada e, em um cenário de atualização da banda C para incluir também a banda L, a banda L tinha preferência no estabelecimento das chamadas desde que todos os enlaces da rota possuíssem fibras ópticas com dispositivos nas duas bandas.…”
Section: Revisão Da Literaturaunclassified